Neutrophils restrain sepsis associated coagulopathy via extracellular vesicles carrying superoxide dismutase 2 in a murine model of lipopolysaccharide induced sepsis - Bao, Wenjie; Xing, Huayue; Cao, Shiwei; Long, Xin; Liu, Haifeng; Ma, Junwei; Guo, Fan; Deng, Zimu; Liu, Xiaolong (Nature communications, 2022)
Disseminated intravascular coagulation (DIC) is a complication of sepsis currently lacking effective therapeutic options. Excessive inflammatory responses are emerging triggers of coagulopathy during sepsis, but the interplay between the immune system and coagulation are not fully understood. Here we utilize a murine model of intraperitoneal lipopolysaccharide stimulation and show neutrophils in the circulation mitigate the occurrence of DIC, preventing subsequent septic death. We show circulating neutrophils release extracellular vesicles containing mitochondria, which contain superoxide dismutase 2 upon exposure to lipopolysaccharide. Extracellular superoxide dismutase 2 is necessary to induce neutrophils’ antithrombotic function by preventing endothelial reactive oxygen species accumulation and alleviating endothelial dysfunction. Intervening endothelial reactive oxygen species accumulation by antioxidants significantly ameliorates disseminated intravascular coagulation improving survival in this murine model of lipopolysaccharide challenge. These findings reveal an interaction between neutrophils and vascular endothelium which critically regulate coagulation in a model of sepsis and may have potential implications for the management of disseminated intravascular coagulation. Disseminated intravascular coagulation is associated with sepsis and a number of inflammatory components have been linked to sepsis associated coagulopathy. Here the authors show neutrophils can prevent lethal coagulopathy via the production of extracellular vesicles that carry superoxide dismutase 2 in a murine model of lipopolysaccharide induced sepsis.